Prospective study for the development of emulsion systems containing natural oil products - Xavier, F. H.; Silva, K. G.H.; Farias, I. E.G.; Morais, A. R.V.; Alencar, E. N.; Araújo, I. B.; Oliveira, A. G. [UNESP]; Egito, E. S.T. (Elsevier, 2012)
Copaiba oil, when used as anti-inflammatory and anti-infective agent, presents two major problems: i) low absorption and bioavailability and ii) an unpleasant taste. Once an appropriate emulsion was achieved, the samples were prepared using different surfactant binary mixtures to obtain a range of HLB values between 45 and 16.5. The HLB value of copaiba oil was 14.8; this system has been stable for more than one year, and the pseudo-ternary diagrams were useful to describe the component proportions. These results indicated that the copaiba oil emulsion might be a promising vehicle for topical delivery of drugs and active cosmetic ingredients.
Keywords: Copaiba oil; Emulsion; Hydrophilic-lipophilic balance; Pseudo-ternary phase diagram; Stability analysis